Soluble programmed cell death-ligand 1 as a new potential biomarker associated with acute coronary syndrome - Li, Shuping; Yi, Ling; Wei, Xiqing; Zhang, Jinguo; Wang, Xiaojue; Jiang, Chang; Yan, Zhuohong; Song, Liwei; Yang, Bin; Wei, Panjian; Gao, Xiang; Wang, Jinghui; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Soluble programmed cell death-ligand 1 (sPD-L1) has been well documented to activate immunosuppression and is considered an essential predictor of negative clinical outcomes for several malignances and inflammatory conditions. However, the clinical signiﬁcance of sPD-L1 in the peripheral blood of patients with coronary artery disease (CAD) remains unclear. The aim of this study was to assess the correlations of sPD-L1 with clinical features in CAD patients and evaluate the diagnostic value of this protein in CAD. Methods: A total of 111 CAD patients and 97 healthy volunteers who served as healthy controls (HCs) were consecutively enrolled. Plasma levels of sPD-L1 were measured with an amplified enzyme-linked immunosorbent assay (ELISA), and hs-CRP was measured with a C-reactive protein assay kit. The levels of other inflammatory cytokines were assessed in 88 CAD patients and 47 HCs by a multiparameter immunoluminescence flow cytometry detection technique. A logistic regression model was used to assess the independent association of sPD-L1 with acute coronary syndrome (ACS). The correlation between sPD-L1 and inflammatory cytokines in ACS was also assessed. Results: Plasma levels of sPD-L1 were signiﬁcantly increased in CAD patients, especially those with ACS. Univariate logistic regression analysis revealed that sPD-L1 (OR: 3.382, 95% CI: 2.249-5.084, p < 0.001), BMI, hypertension, diabetes, dyslipidemai, previous MI, and the levels of HDL-C, LDL-C and hs-CRP were significantly associated with ACS. sPD-L1 (OR: 3.336, 95% CI: 1.084-6.167, p = 0.001) was found to be independently and significantly associated with ACS in the subsequent multivariable logistic regression analysis. Additionally, elevated plasma sPD-L1 levels were associated with increased interleukin-6 and interleukin-8 levels in ACS patients. ROC analysis showed that the AUC of sPD-L1 for diagnosing ACS was 0.778, with a sensitivity of 73.9% and a specificity of 73.4%, which was comparable with that of the inflammatory biomarker hs-CRP. Conclusions: The plasma sPD-L1 level reflects the severity of CAD, is associated with inflammatory responses and is a potential new biomarker for the diagnosis of ACS. Keywords: coronary artery diseases, acute coronary syndrome, inﬂammatory biomarkers, soluble programmed cell death-ligand 1, high-sensitivity C-reactive protein, cytokines